Effects of latex membrane on guided regeneration of long bones - Carlos, Bruna Leonel; Yamanaka, Jessica Suzuki; Yanagihara, Gabriela Rezende; MacedO, Ana Paula; Aranha Watanabe, Plauto Christopher; Mardegan Issa, Joao Paulo; Herculano, Rondinelli Donizetti [UNESP]; Shimano, Antonio Carlos (Taylor & Francis Ltd, 2019)
Natural latex extracted from Hevea brasiliensis is one of the materials pointed out as potential tissue regenerators. The use of latex-based membranes in bone regeneration might be an alternative to stimulate bone formation. The aim of this study was to evaluate the effects of latex membranes in guided bone regeneration of defects produced in long bones of rats. Sixty rats were equally divided into latex and control groups, and each group was subdivided into two subgroups according to treatment duration of 1 and 4 weeks. Bone defects with 2.5 mm in diameter were surgically made in the left tibia. In the animals of the latex group, a latex membrane was placed over the bone defect. The samples underwent quantitative histological analysis of bone formation and collagen matrix, immunohistochemical analysis of osteogenic protein markers, assessment of bone mechanical properties and bone densitometry, and radiological assessment. The osteocalcin immunostaining data were submitted to the generalized linear model test with two independent factors. For the other data, the multivariate ANOVA with two independent factors was performed. The use of the latex membrane significantly improved (p < 0.005) the volume of newly formed bone, collagen type I matrix, expression of osteopontin, and bone stiffness, both in the early and late stages of regeneration. In conclusion, the latex membrane was able to promote bone regeneration in long bones.
Keywords: Latex; Hevea brasiliensis; guided bone regeneration; stereology